Potenciais interações medicamentosas responsáveis por internações hospitalares - Varallo, Fabiana Rossi [UNESP]; Costa, Marília Amaral [UNESP]; de Carvalho Mastroianni, Patrícia [UNESP] (My University, 2013)
Drug-drug interactions (DDI) are considered a public health problem, since they may be the cause of negative outcomes for drug users. Research objectives: 1) estimate the prevalence of hospital admissions arising from potential DDI; 2) identify the signs and symptoms of, as well as risk factors for hospitalization related to, potential DDI. A cross-sectional study was performed in the general clinic of a private hospital in upstate São Paulo, in May 2006, focusing on patients over 18 years old, hospitalized for more than 24 hours, who were interviewed about their symptoms, reasons for hospitalization and the drugs taken prior to hospitalization. The odds ratio was calculated in order to identify risk factors. Results: 168 patients had taken more than one drug, of whom 57 showed potential DDI and, in 17 (10.1%), the signs and symptoms of DDI were probably the reason for hospitalization. The most frequent clinical manifestations of potential DDI were disorders in the cardiovascular (44.3%), digestive (17.2%) and musculoskeletal (13.8%) systems and 10% of the DDI identified were considered potentially hazardous. Risk factors for DDI-motivated hospitalization related to gender, age or the use of drugs with a narrow therapeutic range were not detected. Polypharmacy (p<0.0001) was a determining factor for DDI; conversely, old age was a protection factor (p=0.02). Conclusion: pharmacotherapeutic follow-up of patients who use drugs with a narrow therapeutic range is essential, since these drugs are often involved in hazardous DDI. Pharmacotherapeutic follow-up is also recommended for polymedicated patients, to prevent hospitalization arising from avoidable DDI.
Potential drug interactions responsible for hospital admissions
Keywords: Drug-drug interaction; Drug-related problem; Medication errors; Negative outcome associated with medicines